PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT. QUICKEST COURIER NETWORK WORLDWIDE JAKARTA SELATAN - Siswandi Siswandi (POLITEKNIK LP3I JAKARTA, 2012)
Marketing is a king. It is a slogan for a marketer. the effect of good service has significant corralation. By distributing 30 questioners at 5 regions in Jabodetabek. 20 questions which the writer has distributed for each variable consists of 10 questions about the quality of servive and 10 questions about customer satisfaction. From analysis result coeffecient corralation product moment, it will influence the quality of service to customer satisfaction. It shows corralation (r) 0.62, it means relation between the quality of service (variable x) and customer satisfaction (variable y) has strong relation and positive determinant (r)2 39,44%. It means the effect of the quality of serviceTo the customer satisfaction is 39,44%, maenwhile 61,56% is influenced by facilities and other factors. Kata Kunci : Pelayanan Prima mempengaruhi kepuasan pelanggan